Some Issues of the Development of Constitutional Court Legal Positions in the Context of Guaranteeing Constitutional Stability - Manasyan, A. (Bulletin of Yerevan University C: Jurisprudence, 2019)
The issues of the development of Constitutional Court legal positions in the context of guaranteeing constitutional stability are discussed in the article presented. The author concludes that the approach regarding the mechanical invalidation of the Constitutional Court previous legal positions after constitutional amendments isn’t logical, doesn’t equivalently express the constitutional essence of the mentioned positions and distorts the ideas of constitutional stability, constitutional developments, predictability of the activities of the Constitutional Court and continuity of its practice. Constitutional Court legal positions can be developed, as the formation of the constitutional doctrine isn’t a one-step, but a continuous process. It presupposes the existence of two possible situations: 1. when there is a necessity to fundamentally change the concrete previous legal position of the Constitutional Court, 2. when there is a necessity to broaden the scope of the previous concrete legal position of the Constitutional Court without changing its previous content. In both cases, the main key for the effective solution of the discussed issue is finding a balance between continuity and predictability of the Constitutional Court practice and values, underlying the development of the constitutional doctrine, in each concrete situation.